2012
DOI: 10.14283/jfa.2012.25
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Functional Assessment Instruments and Frailty in Older Adults: The Fradea Study

Abstract: Objectives:To determine the association between functional assessment instruments and frailty.Design:Concurrent cohort study. Setting:Albacete Health Area (Spain). Participants:993 subjects aged ≥ 70years, participating in the FRADEA Study. Measurements:The following functional instruments were applied:Barthel index, Lawton index and Short Form-Late Life Function and Disability Instrument (SF-LLFDI) asdisability questionnaires; Holden ́s Functional Ambulation Classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…It evaluates three physical measurements that include standing balance, walking speed, and chair stands. In this way, it assesses different aspects of physical performance and function of the lower extremities, making it an excellent tool to identify frailty in adults [ 19 ]. The SBBP has many advantages: it requires little training to carry it out, takes only a few minutes to complete, and can be performed in a small space.…”
Section: Discussionmentioning
confidence: 99%
“…It evaluates three physical measurements that include standing balance, walking speed, and chair stands. In this way, it assesses different aspects of physical performance and function of the lower extremities, making it an excellent tool to identify frailty in adults [ 19 ]. The SBBP has many advantages: it requires little training to carry it out, takes only a few minutes to complete, and can be performed in a small space.…”
Section: Discussionmentioning
confidence: 99%
“…However, it might be important for clinicians to find tests that reflect the functional status of their patients. The 5-STS also seems to be a good tool for assessing the frailty (standing up and sitting down can be considered an activity of daily living of the older adults) and the risk of falling [ 61 , 62 ]. To our knowledge, there are no studies in the literature that have analyzed the role of the 5-STS test in older adults with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Given the established relationship between functional decline, disability, and comorbidity, an objective clinical approach to assess physical status is to have a "proxy-frailty" measure based on, for example, the Short Physical Performance Battery (SPPB) 7 . The predictive role of this clinical tool for future disabilities, frailty, and other adverse outcomes including institutionalization, hospital admissions, and mortality has been confirmed in several clinical settings [7][8][9] . The SPPB is, however, essentially a descriptive clinical tool and is therefore unable to assess the molecular/biochemical modifications underlying the loss of functionality.…”
Section: Introductionmentioning
confidence: 86%
“…Guimarães Rocco et al 15 highlighted an SPBB cutoff point ≤ 6 as the most suitable for screening physically frail older people in their sample, with a sensitivity of 0.52, a specificity of 0.70, and an accuracy 0.88. Another study, carried out in Spain, also found that the best cut-off point was ≤ 6, with an area under the curve (AUC) of 0.956 and sensitivity and specificity of 0.88 9 .…”
Section: Clinical and Functional Parametersmentioning
confidence: 94%